Individualised Lifestyle Intervention in Polycystic Ovarian Syndrome Women Who Desire Fertility: A Feasibility Study - Parisuddharao Koduri; Chinta Parimala; Aleyamma Thayparmbil Kunjummen; Bijesh Kumar Yadav; Nitin Kapoor; P. Sandhiya; Vimala; Mohan Shashikant Kamath (Wolters Kluwer Medknow Publications, 2024)
Background: Polycystic ovarian syndrome (PCOS) is one of the common causes of anovulatory infertility among women in the reproductive age group. Women with PCOS and obesity often have difficulty in conceiving, and they are more prone for developing metabolic syndrome. Lifestyle modification plays a key role in women with PCOS, who are overweight or obese and is recommended as a first line management option. The earlier trials evaluating the role of lifestyle intervention in infertile PCOS women had methodological issues, smaller sample size and high dropout rates and none of these trials reported live birth as their outcome. Aim: The current study was planned to explore the feasibility of conducting large adequately powered multicentric trial in future in South Asian women with PCOS who desire fertility. Setting and Design: The study was done in the Department of Reproductive Medicine and Surgery & the Department of Endocrinology and Metabolism at a university level tertiary care hospital. The study is an open label, single center, randomized controlled trial. Materials and Methods: A total of 60 PCOS women aged between 18-40 years with body mass index of > 23 kg/m2 who desire fertility, were randomized to individualized lifestyle intervention and usual care. The primary outcome was the dropout rate, and the secondary outcomes were change in body weight, anthropometric parameters, clinical pregnancy rates and the quality of life specific to PCOS after the trial period. All the participants were followed up for 6 months and the outcomes were assessed. Statistical Analysis: Comparison between the intervention and control groups was done using statistical tests using the SPSS and R software. Results: The dropout rates were significantly higher in the individualized lifestyle intervention arm compared to usual care control arm (19/30, 63% vs 9/30, 30%, P=0.019). We did not find any statistically significant difference in anthropometric measurements, pregnancy rates (P=0.57) and clinical pregnancy rates (P=0.21) and quality of life specific to PCOS compared with sixth month visit from baseline visit. Conclusion: The current feasibility study showed significantly higher dropout rates in individualized lifestyle intervention arm compared to usual care control arm. The knowledge gained from the feasibility study has been used to design an adequately powered trial to evaluate effectiveness of individualized lifestyle intervention in women with PCOS who wish to conceive.